Role of RUNX2 in Oral Squamous Cell Carcinoma (OSCC): A Systematic Scoping Review - AL-Hamad, Khalid A. (European Journal of Cancer Care, 2024)
RUNX2, known as the core-binding factor subunit alpha-1 (Cbfa1), is a protein-coding gene recognized and responsible for its involvement in bone development and osteoblast differentiation. However, its dysregulation and aberrant expression have been linked to the pathogenesis of many diseases, such as oral squamous cell carcinoma (OSCC). This review highlights the significance of the RUNX2 gene in oral squamous cell carcinoma. Objectives. To review the contribution of the RUNX2 gene in oral squamous cell carcinoma and its implication on clinical diagnosis and treatments. Materials and Methods. A systematic scoping review was conducted to elucidate the role of RUNX2 in OSCC. A framework of five stages for scoping reviews outlined by Arksey and O’Malley (2005) was adopted for the current study. Results. The review showed that RUNX2 plays a role in the development and progression of OSCC, a common form of head and neck cancer. Conclusion. RUNX2 is an essential player in the molecular mechanisms underlying the development and progression of oral squamous cell carcinoma, and its dysregulation promotes tumor initiation, progression, and metastasis, making it a potential target therapy for future research aimed at developing novel therapies for oral squamous cell carcinoma. Clinical Relevance. Understanding the precise mechanisms by which RUNX2 contributes to OSCC pathogenesis can lead to target treatment for this challenging form of cancer.